2019
DOI: 10.1080/00140139.2018.1531149
|View full text |Cite
|
Sign up to set email alerts
|

Elite handcycling: a qualitative analysis of recumbent handbike configuration for optimal sports performance

Abstract: Our understanding of handbike configuration is limited, yet it can be a key determinant of performance in handcycling. This study explored how fourteen handcycling experts (elite handcyclists, coaches, support staff and manufacturers) perceived aspects of recumbent handbike configuration to impact upon endurance performance via semi-structured interviews. Optimising the handbike for comfort, stability and power production were identified as key themes. Comfort and stability were identified to be the foundation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Before starting the experiment, a number of calibrations were recorded to determine the locations of anatomical landmarks and the joint centre of the glenohumeral joint [25]. Thereafter, the C7 and T8 markers were replaced with virtual markers (in respect to the thorax cluster) during the handcycling trials due to marker occlusion caused by the participant’s recumbent position [9,20]. The identified landmarks were; the sternoclavicular joint, the acromioclavicular joint, the acromion angle, trigonium spinae, the inferior angle of the scapula, and the medial and lateral epicondyle of the humerus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before starting the experiment, a number of calibrations were recorded to determine the locations of anatomical landmarks and the joint centre of the glenohumeral joint [25]. Thereafter, the C7 and T8 markers were replaced with virtual markers (in respect to the thorax cluster) during the handcycling trials due to marker occlusion caused by the participant’s recumbent position [9,20]. The identified landmarks were; the sternoclavicular joint, the acromioclavicular joint, the acromion angle, trigonium spinae, the inferior angle of the scapula, and the medial and lateral epicondyle of the humerus.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, numerous areas of the handcycle-user interface can be manipulated, such as the backrest inclination [35], crank length [57] or handgrip orientation [7,8]. A recent qualitative study with expert handcyclists and coaches identified the horizontal displacement of the crank-axis with respect to the athlete, known as the crank fore-aft position, to be a key area of handcycle configuration with regards to performance [9]. A parallel can be made with wheelchair seat-height studies that similarly looked at the axle position with respect to the upper body, which showed that gross mechanical efficiency at a given task-load can be optimized through changes in wheelchair configuration [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, since the experimental designs of these studies varied considerably, using attachable-units, touring handbikes or bespoke ergometers, this makes the findings difficult to transfer to the recumbent handbikes used in the present day. These handbikes are considerably lighter, but more importantly, are bespoke to the individual, with respect to crank position, crank width and backrest inclination (Stone et al 2018). Therefore, the purpose of this study was to characterise the physiological profiles of trained handcyclists, during recumbent handcycling and to identify which physiological variables are related to 16 km TT performance.…”
Section: Introductionmentioning
confidence: 99%
“…This was evidenced by an increase in RoM and SDs when compared to the competitive handcyclists. Maintaining a stable thorax position was identified to be a critical component of the handbike‐user interface and was perceived to have a substantial impact on performance . Although sagittal, frontal and transverse plane RoM of the thorax was low (<7°), which was comparable to the 5°‐10° previously reported, a reduction in thorax RoM could indicate an improvement in technique or handbike configuration.…”
Section: Discussionmentioning
confidence: 53%